2007
DOI: 10.1152/ajpendo.00493.2006
|View full text |Cite
|
Sign up to set email alerts
|

An increase in in vivo release of LHRH and precocious puberty by posterior hypothalamic lesions in female rhesus monkeys (Macaca mulatta)

Abstract: We have previously shown that a decrease in ␥-aminobutyric acid (GABA) tone and a subsequent increase in glutamatergic tone occur in association with the pubertal increase in luteinizing hormone releasing hormone (LHRH) release in primates. To further determine the causal relationship between developmental changes in GABA and glutamate levels and the pubertal increase in LHRH release, we examined monkeys with precocious puberty induced by lesions in the posterior hypothalamus (PH). Six prepubertal female rhesu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…With respect to GABA effects on GnRH release, GABA containing terminals synapse directly with GnRH neurons in the rat (Leranth et al, 1985), whereas synaptic contact between GABAergic neurons and GnRH neurons has not been detected in the rhesus macaque (Thind and Goldsmith, 1995). In the macaque, it is possible that other mechanisms may intercede between GABA and GnRH (Windsor-Engnell et al, 2007). Estrogen regulation of regional GABA concentrations has long been implicated in the feedback action of estrogen on gonadotropin release (Mansky et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to GABA effects on GnRH release, GABA containing terminals synapse directly with GnRH neurons in the rat (Leranth et al, 1985), whereas synaptic contact between GABAergic neurons and GnRH neurons has not been detected in the rhesus macaque (Thind and Goldsmith, 1995). In the macaque, it is possible that other mechanisms may intercede between GABA and GnRH (Windsor-Engnell et al, 2007). Estrogen regulation of regional GABA concentrations has long been implicated in the feedback action of estrogen on gonadotropin release (Mansky et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate receptors are present in the median eminence, as shown by immunohistochemistry [ 4 , 15 , 16 ]. Perifusion and push-pull perfusion studies of this region also show that glutamate is released [ 45 , 46 ]. Recent morphological and functional study of GnRH identified that the GnRH “dendron”, which has a mixed phenotype of dendrites and axons, is responsive to glutamate stimulation within and near the median eminence [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, very similar to maternal behaviors, lesions of the entire mammillary region and surrounding tissue do not eliminate copulation in male rats, but rather, disinhibit it (Lisk, 1966, 1969). Lastly, female rhesus monkeys with posterior hypothalamic lesions extending into the mammillary bodies show advanced puberty (Terasawa et al, 1984; Windsor-Engnell et al, 2007), the onset of which involves DAergic influence in the mPOA (Wuttke et al, 1980; Docke et al, 1987). Thus, DAergic projections from the PHv and mammillary region to the mPOA may be an important contributor to the balance of inhibitory and excitatory inputs influencing a range of reproductive processes.…”
Section: Discussionmentioning
confidence: 99%